Language of Communication as an Important Condition for the Development of National Identity During Ukrainian Students - Lyubov Spivak; Olena Kovalenko (Психолінгвістика, 2018)
The article is dedicated to such an important condition for the development of the national identity of Ukraine higher educational institution students as the language of their communication. The author’s understanding of the psychological nature of the phenomenon of “national identity” is presented which consists of understanding and evaluating by the personality one’s own nationality. Personality’s national identity is the result of the awareness of its own affiliation with a certain nation and its emotional evaluation of this membership. The students’ age is sensitive to the development of personality national identity. The main psychological positions of scientists about the conditions of development of national identity, in particular the language of communication, are presented. O. Potebni and D. Ovsyaniko-Kulikovsky works dedicated to the importance of the language of communication in the development of the national identity of Ukrainians are presented. The language of communication of Ukrainian students with significant others (relatives, friends, peers) is empirically determined and their types of national identity are determined. It is proved that the main condition for the development of positive national identity of Ukraine higher educational institution students is their communication with other significant others by means of the national language. It is revealed that most students with a positive national identity speak just Ukrainian with their significant others, or they speak several languages – more often Ukrainian and rarely in Russian and English. The prospects for further research are seen in the study of the influence of other nation features on the development of the Ukrainian student’s national identity and the influence of cross cultural features of the language of communication on the student’s national identity development.